Circulating CTRP1 Levels in Type 2 Diabetes and Their Association with FGF21. (23rd May 2016) - Han, Sora; Kim, Jong Dai; Lee, Sunyi; Jeong, Ae Lee; Park, Jeong Su; Yong, Hyo Jeong; Boldbaatar, Ariundavaa; Ka, Hye In; Rhee, Eun-Jung; Lee, Won-Young; Yang, Young
Abstract : The goal of this study was to investigate whether circulating C1q/TNF- α -related protein 1 (CTRP1) levels are associated with diabetes. In addition, relationships between CTRP1 and other diabetes-related cytokines were elucidated, including adiponectin and fibroblast growth factor 21 (FGF21). A total of 178 subjects (78 men and 100 women) aged 29–70 years (mean age, 46.1 years) were randomly selected. The sera from a normal glucose tolerance group (n = 68 ) and a prediabetes/type 2 diabetes group (n = 1 10 ) were collected; then, circulating levels of CTRP1, adiponectin, and FGF21 were determined via enzyme-linked immunosorbent assay in all sera. Subjects with either prediabetes or diabetes exhibited higher circulating CTRP1 levels than healthy subjects. Sera analysis revealed that CTRP1 was positively correlated with age, body mass index, fasting blood glucose, and circulating FGF21 levels. However, CTRP1 was negatively correlated with total cholesterol and total circulating adiponectin levels in univariate analysis. In addition, multivariate analysis found that CTRP1 was independently associated with age, fasting blood glucose, and circulating FGF21 levels. CTRP1 was correlated with homeostasis model assessment- β (HOMA- β ), but no correlation was observed with HOMA-insulin resistance. In conclusion, circulating CTRP1 levels are increased in subjects with type 2 diabetes and are positively associated with circulating FGF21 levels.